2017
DOI: 10.1016/j.jchemneu.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies comparison of the functional characteristics of plasma membrane monoamine transporter (PMAT) between human, rat and mouse

Abstract: Plasma membrane monoamine transporter (PMAT) is a newly discovered monoamine transporter belonging to the equilibrative nucleoside transporter family. Highly expressed in the brain, PMAT represents a major uptake2 transporter that may play a role in monoamine clearance. Although human PMAT has been functionally characterized at the molecular level, rodent models are often used to evaluate PMAT function in ex vivo and in vivo studies. The aim of this study was to examine if there is potential species difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
(47 reference statements)
0
10
1
Order By: Relevance
“…Mouse models are an essential preclinical resource to study the action of low-affinity transporters. Functional similarities have been observed between the uptake kinetics of substrates like dopamine, MPP + , and serotonin by human and mouse PMAT (Miura et al, 2017; Shirasaka et al, 2016). On the other hand, hOCT3 and mOCT3 were found to share similar affinities for MPP + , but not serotonin (Massmann et al, 2014).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Mouse models are an essential preclinical resource to study the action of low-affinity transporters. Functional similarities have been observed between the uptake kinetics of substrates like dopamine, MPP + , and serotonin by human and mouse PMAT (Miura et al, 2017; Shirasaka et al, 2016). On the other hand, hOCT3 and mOCT3 were found to share similar affinities for MPP + , but not serotonin (Massmann et al, 2014).…”
Section: Discussionmentioning
confidence: 89%
“…Earlier work established D22 as a potent inhibitor of low-affinity/high-capacity transporters, including OCT2, OCT3, and PMAT (Gasser et al, 2009; Hayer-Zillgen, Brüss, & Bönisch, 2002; Russ, H., Gliese, Sonna, & Schömig, 1992; Russ, H. et al, 1993; Russ, H., Sonna, Keppler, Baunach, & Schömig, 1993; Russ, Hermann, Staudt, Martel, Gliese, & Schomig, 1996; Schomig, Babin-Ebell, & Russ, 1993; Shirasaka et al, 2016; Sun et al, 2014; Wang, Sun, Li, Tu, & Jiang, 2014; Zhang, Schaner, & Giacomini, 1998). In line with prior D22 action at hOCT3 (Hayer-Zillgen et al, 2002), we found that D22 was a more potent inhibitor of [ 3 H]MPP + uptake at hOCT3 (IC 50 ≈ 0.2 μM) than hOCT2 (IC 50 ≈ 10 μM) and extended this finding to hPMAT (IC 50 ≈ 1 μM).…”
Section: Discussionmentioning
confidence: 99%
“…This might explain why knockout behaviour more closely resembles that of wild‐types in the elevated plus maze, whereas partial deletion of PMAT in heterozygotes might not be sufficient to elicit this compensatory upregulation and thereby could reveal a more accurate representation of constitutive PMAT deficiency. Such mice could provide valuable models of reduced PMAT function (Shirasaka et al., ), as recently two SLC29A4 polymorphisms conferring loss of function have been discovered in humans (Adamsen et al., ). Indeed, deficiency of PMAT may not become overtly evident in behaviours until monoaminergic systems are sufficiently perturbed.…”
Section: Discussionmentioning
confidence: 99%
“…73) As suggested by these reports, even though the physiological roles of OCT3 and PMAT appear to be mostly conserved among species, their inhibitor (and substrate) recognition preference must be, at least slightly, different, depending on their intrinsic amino acid sequences.…”
Section: Cautionary Notes On Astrocyte Organic Ion Transporter Studiesmentioning
confidence: 92%